![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
c/
\(\Leftrightarrow\sqrt{3}tan\left(\frac{\pi}{9}-2x\right)=-3\)
\(\Leftrightarrow tan\left(\frac{\pi}{9}-2x\right)=-\sqrt{3}\)
\(\Rightarrow\frac{\pi}{9}-2x=-\frac{\pi}{3}+k\pi\)
\(\Rightarrow x=\frac{2\pi}{9}+\frac{k\pi}{2}\)
d/
\(\Leftrightarrow\left[{}\begin{matrix}tanx=5\\tan2x=tan4\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=arctan\left(5\right)+k\pi\\2x=4+k\pi\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=arctan\left(5\right)+k\pi\\x=2+\frac{k\pi}{2}\end{matrix}\right.\)
a/
ĐKXĐ: ...
\(\Leftrightarrow tanx-8\sqrt{3}=3tanx-6\sqrt{3}\)
\(\Leftrightarrow2tanx=-2\sqrt{3}\)
\(\Rightarrow tanx=-\sqrt{3}\Rightarrow x=-\frac{\pi}{3}+k\pi\)
b/
\(\Leftrightarrow tan2x=-cot\left(\frac{5\pi}{8}\right)\)
\(\Leftrightarrow tan2x=tan\left(\frac{\pi}{2}+\frac{5\pi}{8}\right)\)
\(\Leftrightarrow tan2x=tan\left(\frac{9\pi}{8}\right)\)
\(\Rightarrow2x=\frac{9\pi}{8}+k\pi\Rightarrow x=\frac{9\pi}{16}+\frac{k\pi}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
c/
\(\Leftrightarrow tan\left(60^0-x\right)=-\frac{1}{\sqrt{3}}\)
\(\Rightarrow60^0-x=-30^0+k180^0\)
\(\Rightarrow x=90^0+k180^0\)
d/
\(\Leftrightarrow tan\left(3x+\frac{2\pi}{5}\right)=-tan\left(\frac{\pi}{5}\right)\)
\(\Leftrightarrow tan\left(3x+\frac{2\pi}{5}\right)=tan\left(-\frac{\pi}{5}\right)\)
\(\Rightarrow3x+\frac{2\pi}{5}=-\frac{\pi}{5}+k\pi\)
\(\Rightarrow x=-\frac{\pi}{5}+\frac{k\pi}{3}\)
a/
\(\Leftrightarrow tan2x=-tan40^0\)
\(\Leftrightarrow tan2x=tan\left(-40^0\right)\)
\(\Rightarrow2x=-40^0+k180^0\)
\(\Rightarrow x=-20^0+k90^0\)
b/
\(\Leftrightarrow tan\left(2x-15^0\right)=1\)
\(\Rightarrow2x-15^0=45^0+k180^0\)
\(\Rightarrow x=30^0+k90^0\)
![](https://rs.olm.vn/images/avt/0.png?1311)
c/
ĐKXĐ: ...
\(\Leftrightarrow tan2x-2=3\left(2tan2x+1\right)\)
\(\Leftrightarrow5tan2x=-5\)
\(\Rightarrow tan2x=-1\)
\(\Rightarrow2x=-\frac{\pi}{4}+k\pi\)
\(\Rightarrow x=-\frac{\pi}{8}+\frac{k\pi}{2}\)
d/
ĐKXĐ: ...
\(\Leftrightarrow sinx+\sqrt{3}cosx=3sinx-\sqrt{3}cosx\)
\(\Leftrightarrow2sinx=2\sqrt{3}cosx\)
\(\Rightarrow tanx=\sqrt{3}\Rightarrow x=\frac{\pi}{3}+k\pi\)
a/
\(\Leftrightarrow tanx=-tan\left(\frac{2\pi}{3}-3x\right)\)
\(\Leftrightarrow tanx=tan\left(3x-\frac{2\pi}{3}\right)\)
\(\Rightarrow x=3x-\frac{2\pi}{3}+k\pi\)
\(\Rightarrow x=\frac{\pi}{3}+\frac{k\pi}{2}\)
b/
\(tan\left(2x-15^0\right)=tanx\)
\(\Rightarrow2x-15^0=x+k180^0\)
\(\Rightarrow x=15^0+k180^0\)
![](https://rs.olm.vn/images/avt/0.png?1311)
c/
\(a+b+c=1+\sqrt{3}-1-\sqrt{3}=0\)
\(\Rightarrow\) Pt có 2 nghiệm: \(\left[{}\begin{matrix}tanx=1\\tanx=-\sqrt{3}\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=\frac{\pi}{4}+k\pi\\x=-\frac{\pi}{3}+k\pi\end{matrix}\right.\)
d/ ĐKXĐ: ...
\(\Leftrightarrow cot^22x+3.cot2x+2=0\)
\(\Leftrightarrow\left[{}\begin{matrix}cot2x=-1\\cot2x=-2\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}2x=-\frac{\pi}{4}+k\pi\\2x=arccot\left(-2\right)+k\pi\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=-\frac{\pi}{8}+\frac{k\pi}{2}\\x=\frac{1}{2}arccot\left(-2\right)+\frac{k\pi}{2}\end{matrix}\right.\)
a/
\(\Leftrightarrow2cos^2x-1+cosx+1=0\)
\(\Leftrightarrow cosx\left(2cosx+1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}cosx=0\\cosx=-\frac{1}{2}\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=\frac{\pi}{2}+k\pi\\x=\pm\frac{2\pi}{3}+k2\pi\end{matrix}\right.\)
b/ ĐKXĐ: ...
\(\Leftrightarrow tanx+\frac{1}{tanx}=2\)
\(\Leftrightarrow tan^2x+1=2tanx\)
\(\Leftrightarrow tan^2x-2tanx+1=0\)
\(\Leftrightarrow tanx=1\Rightarrow x=\frac{\pi}{4}+k\pi\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{tanx-1}{tanx+1}+cot2x=0\\ \Leftrightarrow cot2x-\frac{1-tanx\cdot tan\frac{\pi}{4}}{tanx+tan\frac{\pi}{4}}=0\\ \Leftrightarrow cot2x-cot\left(x+\frac{\pi}{4}\right)=0\)
d/
ĐKXĐ: \(\left\{{}\begin{matrix}sin2x\ne0\\tanx\ne-1\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}x\ne\frac{k\pi}{2}\\x\ne-\frac{\pi}{4}+k\pi\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}\frac{tanx-1}{tanx+1}+cot2x=0\\3tanx-\sqrt{3}=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}\frac{tanx-1}{tanx+1}-\frac{tan^2x-1}{2tanx}=0\\tanx=\frac{\sqrt{3}}{3}\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}\left(tanx-1\right)\left(\frac{1}{tanx+1}-\frac{tanx+1}{2tanx}\right)=0\left(1\right)\\x=\frac{\pi}{6}+k\pi\end{matrix}\right.\)
Xét (1): \(\Leftrightarrow\left[{}\begin{matrix}tanx=1\Rightarrow x=\frac{\pi}{4}+k\pi\\\frac{1}{tanx+1}-\frac{tanx+1}{2tanx}=0\left(2\right)\end{matrix}\right.\)
Xét (2)
\(\Leftrightarrow\left(tanx+1\right)^2-2tanx=0\)
\(\Leftrightarrow tan^2x+1=0\left(vn\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
ĐKXĐ: ...
Sử dụng công thức \(tana+tanb=\frac{sin\left(a+b\right)}{cosa.cosb}\) ta có:
\(tan\left(\frac{\pi}{3}-4x\right)+tan\left(\frac{\pi}{6}+x\right)=\frac{cosx}{sinx}-\frac{sin2x}{cos2x}\)
\(\Leftrightarrow\frac{sin\left(\frac{\pi}{2}-3x\right)}{cos\left(\frac{\pi}{3}-4x\right)cos\left(\frac{\pi}{6}+x\right)}=\frac{cos2x.cosx-sin2x.sinx}{sinx.cos2x}\)
\(\Leftrightarrow\frac{cos3x}{cos\left(\frac{\pi}{3}-4x\right)cos\left(\frac{\pi}{6}+x\right)}=\frac{cos3x}{sinx.cos2x}\)
\(\Leftrightarrow\left[{}\begin{matrix}cos3x=0\Rightarrow...\\cos\left(\frac{\pi}{3}-4x\right)cos\left(\frac{\pi}{6}+x\right)=sinx.cos2x\left(1\right)\end{matrix}\right.\)
\(\left(1\right)\Leftrightarrow cos\left(\frac{\pi}{2}-3x\right)+cos\left(\frac{\pi}{6}-5x\right)=sin3x-sinx\)
\(\Leftrightarrow sin3x+cos\left(\frac{\pi}{6}-5x\right)=sin3x-sinx\)
\(\Leftrightarrow cos\left(\frac{\pi}{6}-5x\right)=-sinx=cos\left(\frac{\pi}{2}+x\right)\)
\(\Leftrightarrow\left[{}\begin{matrix}\frac{\pi}{6}-5x=\frac{\pi}{2}+x+k2\pi\\\frac{\pi}{6}-5x=-\frac{\pi}{2}-x+k2\pi\end{matrix}\right.\)
\(\Leftrightarrow...\)
ĐKXĐ: ...
\(\Leftrightarrow\frac{6tanx}{1-tan^2x}-3tanx-\frac{5}{2}=0\)
\(\Leftrightarrow12tanx-6tanx\left(1-tan^2x\right)-5=0\)
\(\Leftrightarrow6tan^3x+6tanx-5=0\)
Bạn coi lại đề :)